Springback prediction model of Ti-6Al-4V tube warm bending based on modified JC model considering variable temperature field. Issue 1 (1st December 2022) - Wang, L; Wang, Z L; Zhang, S Y; Lin, Y C; Fu, M Y
Abstract : The plastic forming of titanium alloy tubes at room temperature exhibits strong anisotropy, low elongation, and large deformation resistance. Numerical control warm bending assisted forming technology can improve the stability of the titanium alloy tube bending process, increase the bending limit and reduce the springback angle. This technology promotes the wide application of high-precision titanium alloy bent tubes in many high-end fields such as aerospace, shipbuilding, chemical industry, and military industry. However, the titanium alloy tube bending at high temperatures involves complex material rheological behavior and microstructure characteristics. The coupling relationship between the stress-strain properties of the material and the temperature field makes it difficult to predict the springback behavior of titanium alloy tubes after warm bending. In this paper, based on the mechanical behavior of titanium alloy tubes at high temperatures, a constitutive model of titanium alloy suitable for local heating is improved. The theoretical model of springback for warm rotary draw bending of titanium alloy tube is established. The influence of warm bending strategies on the springback of bending is studied. The theoretical model is verified by establishing a thermal-mechanical coupling finite element model for the whole process of warm bending under the state of heat balance. The results show that the bending springback theory based on the modified John-Cook model can accurately simulate the temperature change of titanium alloy tube section, adapt to local heating strategies and provide high prediction accuracy of bending springback.